Open Innovation—Opportunities or Nightmares for the Shared Transport Services Sector? - Katarzyna Turoń; Andrzej Kubik (Journal of Open Innovation: Technology, Market and Complexity, 2022)
ABSTRACT: Shared transport services, including short-term vehicle rentals (bike-, car-, moped-, scooter-sharing) and travel sharing systems (ride-sharing, ride-hailing), have become more and more popular forms of mobility in recent years. Their increasing availability has made them an alternative to individual transport in cities. Along with the development of the systems, a growing number of operators offering sharing services started to appear. Many of them ended their activities after the pilot period or closed the company shortly after launching the system. There are many reasons for this, from management to technical issues, but the aspects of open innovation, open data and transparency were often overlooked. This begs the question whether it is the openness of systems that is the recipe for the market success or failure of shared mobility services. The aim of this work was to evaluate the approaches to data openness and innovation in companies representing the shared mobility market. A research proposal was submitted to diagnose the approach to open innovations in the market of shared mobility services. An expert survey was carried out among representatives of shared mobility services operating in major Polish cities. The expert survey was conducted using the CAWI technique. Research results show that open innovation is a problematic aspect for operators. On the one hand, they are interested in it, but this interest does not translate into real practices. Among the entire shared transport sector, the micro-mobility service providers are the most committed to open innovation. Research indicates that in order to increase the dynamics of the development of open innovation in the shared transport industry, there is a need for education in the field of open innovation, especially in the era of the development of digitization of urban transport systems and the pursuit of sustainable transport.